A New Method for Computing the Weighted Generalized Inversion of Partitioned Matrices (Journal of Computational Mathematics, 2021)
In this paper, we shall give a new method for computing the weighted generalized inversion of partitioned matrices, i.e. solve the weighted problems with the aid of the unweighted ones, which is quite efficient and convenient for either dealing with the inconsistent equations or computing the generalized inverses, now we discuss some problems about the latter. The theorem I below is an extension of the main result in [2], especially, the proof is quite succinct here.